Comparative study of acupressure wristband versus palonosetron for prophylaxis of postoperative nausea and vomiting in elective laparoscopic cholecystectomy under general anaesthesia - Naik, Suchismita; Kujur, Shweta; Debbarma, Miltan; Debbarma, Miltan; Murthy, Madhumita G. (International Journal of Research in Medical Sciences, 2016)
Background: Postoperative nausea and vomiting (PONV) is common complication after general anesthesia and surgery. This randomized double-blind study was designed to compare the effects of acupressure wrist bands and palonosetron for the prevention of post-operative nausea and vomiting (PONV) in laparoscopic cholecystectomy under general anaesthesia. Methods: Sixty ASA I and II patients undergoing elective laparoscopic surgeries under general anaesthesia were divided into two groups. In Group A patients, acupressure wrist bands were applied on p6 point on both hands half an hour before induction. Group P patients received inj. palonosetron 0.075 m.g. i.v. just before induction. Anaesthesia technique was standardized. Post-operatively patients were monitored for nausea, retching or vomiting upto 24 hours. If patients vomited more than once, they were given inj. Metoclopramide 10mg as rescue antiemetic. Efficacy of drugs was compared using Chi square test. ‘p’ value of <0.05 is considered significant. Results: The incidence of PONV and requirement of rescue antiemetic were lower in palonosetron group than acupressure wrist band group. Conclusions: Palonosetron is more effective than acupressure wrist band for prophylaxis of post- operative nausea and vomiting in the patients undergoing laparoscopic cholecystectomy under general anaesthesia, but acupressure wrist band can also be used as an alternative non-pharmacological method.